Computer Simulation of Automobile Fires - Ladislav Halada; Peter Weisenpacher; Gabriel Oksa; Jan Glasa; Martin Becka (Communications - Scientific letters of the University of Zilina, 2011)
Using CFD (Computer Fluid Dynamics) theory and its practical knowledge has become widespread in such academic disciplines as aerodynamics, fluid dynamics, combustion engineering and other fields. However, in disciplines, which examine the ongoing processes in larger sizes, CFD was applied during the last decade only. One of such discipline is a spread of fire. Fire processes are a very complicated and complex phenomenon consisting of combustion, radiation, turbulence, fluid dynamics, pressure and other physical and chemical processes. In the paper, we describe the use of FDS (Fire Dynamics Simulator) for the simulation of automobile/vehicle fires in different environment.